Nurse resilience: A concept analysis - Cooper, Alannah L.; Brown, Janie A.; Rees, Clare S.; Leslie, Gavin D. (International journal of mental health nursing, 2020)
Nurse resilience is attracting increasing attention in research and practice. Possession of a high level of resilience is cited as being crucial for nurses to succeed professionally and manage workplace stressors. There is no agreed definition of nurse resilience. A concept analysis was undertaken to examine nurse resilience using a priori selected analysis framework. This concept analysis aims to systematically analyse resilience as it relates to nurses and establish a working definition of nurse resilience. Sixty‐nine papers met the search criteria for inclusion. Key attributes of nurse resilience were social support, self‐efficacy, work–life balance/self‐care, humour, optimism, and being realistic. Resilience enables nurses to positively adapt to stressors and adversity. It is a complex and dynamic process which varies over time and context and embodies both individual attributes and external resources. Sustaining nurse resilience requires action and engagement from both individuals and organizations.